Non-classical gluconeogenesis-dependent glucose metabolism in Rhipicephalus microplus embryonic cell line BME26 - Silva, R.M. da; Noce, B.D.; Waltero, C.F.; Costa, E.P.; Abreu, L.A. de; Githaka, Naftaly W.; Moraes, J.; Gomes, H.F.; Konnai, S.; Silva Vaz, I. da; Ohashi, K.; Logullo, C. (MDPI, 2015)
In this work we evaluated several genes involved in gluconeogenesis, glycolysis and glycogen metabolism, the major pathways for carbohydrate catabolism and anabolism, in the BME26 Rhipicephalus microplus embryonic cell line. Genetic and catalytic control of the genes and enzymes associated with these pathways are modulated by alterations in energy resource availability (primarily glucose). BME26 cells in media were investigated using three different glucose concentrations, and changes in the transcription levels of target genes in response to carbohydrate utilization were assessed. The results indicate that several genes, such as glycogen synthase (GS), glycogen synthase kinase 3 (GSK3), phosphoenolpyruvate carboxykinase (PEPCK), and glucose-6 phosphatase (GP) displayed mutual regulation in response to glucose treatment. Surprisingly, the transcription of gluconeogenic enzymes was found to increase alongside that of glycolytic enzymes, especially pyruvate kinase, with high glucose treatment. In addition, RNAi data from this study revealed that the transcription of gluconeogenic genes in BME26 cells is controlled by GSK-3. Collectively, these results improve our understanding of how glucose metabolism is regulated at the genetic level in tick cells.